Association of Deep versus Moderate Neuromuscular Blockade with Surgical Conditions and Postoperative Pulmonary Complications: A Systematic Review of Randomized Controlled Trials - Pretika Prameswari; Raka Jati Prasetya; Mutia Juliana (International Medical Journal Corp. Ltd, 2025)
Introduction: The optimal depth of intraoperative neuromuscular blockade (NMB) remains a subject of clinical debate. Deep NMB is hypothesized to improve surgical conditions, particularly in minimally invasive surgery, but has historically been associated with an increased risk of postoperative pulmonary complications (PPCs) due to residual neuromuscular blockade (rNMB). This systematic review evaluates the evidence from randomized controlled trials (RCTs) to compare the effects of deep versus moderate NMB on surgical conditions and the incidence of PPCs. Methods: A systematic search of PubMed, Embase, and the Cochrane Central Register of Controlled Trials was conducted to identify RCTs comparing deep NMB (defined as a post-tetanic count of 1-2) with moderate NMB (defined as a train-of-four count of 1-2) in adult surgical patients. Primary outcomes were measures of surgical conditions (e.g., surgical rating scales, intraoperative patient movement) and the incidence of a composite of PPCs (e.g., pneumonia, atelectasis, respiratory failure). Secondary outcomes included postoperative pain, opioid consumption, recovery times, and other adverse events. Methodological quality was assessed using the Cochrane Risk of Bias 2 tool. Results: Seventeen RCTs met the inclusion criteria. The evidence consistently demonstrated that deep NMB was significantly associated with improved surgical conditions, including higher surgeon-rated scores, a significantly lower incidence of intraoperative patient movement, and the facilitation of lower intra-abdominal pressures during laparoscopy. Regarding safety, when deep NMB was managed with quantitative neuromuscular monitoring and reversed with appropriate agents, particularly sugammadex, there was no statistically significant increase in the incidence of composite PPCs, pneumonia, or atelectasis compared to moderate NMB. Furthermore, deep NMB was significantly associated with beneficial secondary outcomes, including reduced postoperative pain scores, lower opioid consumption, and a decreased incidence of postoperative nausea and vomiting. Discussion: The findings suggest a clear dissociation between the intraoperative depth of NMB and postoperative pulmonary risk. The primary driver of PPCs is postoperative rNMB, a risk that can be effectively mitigated with precise neuromuscular monitoring and the use of reversal agents capable of reliably antagonizing deep block. The benefits of deep NMB on surgical quality are substantial and are complemented by improvements in postoperative pain and recovery metrics. Conclusion: Deep NMB provides significant intraoperative advantages over moderate NMB, enhancing surgical conditions and safety. When implemented as part of a comprehensive strategy that includes quantitative monitoring and effective pharmacological reversal to prevent residual paralysis, it is not associated with an increased risk of postoperative pulmonary complications and may improve aspects of postoperative recovery.